Casa Grande, Front Facade exterior elevation - Julia Morgan::::::::: (1921)
Early drawing by Julia Morgan of the hilltop, looking east, with House A, House B, and House C, and Casa Grande with two towers. In the lower right corner Morgan writes: "Rough sketch of house locations as per last telegram - JM. Some liberty taken with exteriors--how do you like the idea? With the long towers it might be very effective." Upper right corner, Hearst responds: "This idea of loggia and stairs I have put on house C. I think it makes a good motif for the middle house WRH"